ESSENTIAL PARAMETERS IN SUCCESSFUL VERMICULTURE PRACTICES (International Journal of Food and Nutritional Sciences, 2022)
An attempt has been made to study the methodologies that are essential parameters in successfulvermiculture practices Vermiculture which is the cultivation of worms for agriculture purposes. The literalmeaning of vermiculture is worms are used for compost formation and called vermicomposting. In generalearthworms are nocturnal and feed on organic matter. Factors such as soil, temperature, moisture, mineralcontent aeration and availability of food, reproductive potential and adaptability are essential, theseearthworms live in different levels in soil strata. perionyx excavatus is tolerant to wide range of temperaturefound in tropical countries drawida shows high affinity for high moisture conditions dichogaster and lamptomauritius need moderate moisture content. Worms feed on leaf litter, organic humus, dung, compost, effluent,vegetative parts, fruit peels and every type of biologically degradable waste. Majority of worms are organicmatter feeders except a carnivorous species of a gastrodrillus. This study shows if proper methodologies wereused in vermiculture would gives good results in production of vermicompost.